2012 IEEE International Symposium on Performance Analysis of Systems &Amp; Software 2012
DOI: 10.1109/ispass.2012.6189225
|View full text |Cite
|
Sign up to set email alerts
|

FPGA modeling of diverse superscalar processors

Abstract: There is increasing interest in using Field Programmable Gate Arrays (FPGAs) as platforms for computer architecture simulation. This paper is concerned with modeling superscalar processors with FPGAs. To be transformative, the FPGA modeling framework should meet three criteria.(1) Configurable: The framework should be able to model diverse superscalar processors, like a software model. In particular, it should be possible to vary superscalar parameters such as fetch, issue, and retire widths, depths of pipelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…While the trends described in the previous section solve the availability and FPGA capacity challenges, usability remains a problem. Previous work [7,12] has shown that much of an FPGA-accelerated simulator can be automatically generated from source RTL. This Session 9: Memory FPGA '19, February 24-26, 2019, Seaside, CA, USA RTL can be written in an HDL like Verilog, generated by a high-level synthesis tool, or emitted by languages like Chisel [3] or Bluespec.…”
Section: Usability Through Automationmentioning
confidence: 99%
“…While the trends described in the previous section solve the availability and FPGA capacity challenges, usability remains a problem. Previous work [7,12] has shown that much of an FPGA-accelerated simulator can be automatically generated from source RTL. This Session 9: Memory FPGA '19, February 24-26, 2019, Seaside, CA, USA RTL can be written in an HDL like Verilog, generated by a high-level synthesis tool, or emitted by languages like Chisel [3] or Bluespec.…”
Section: Usability Through Automationmentioning
confidence: 99%
“…The majority of academic research in the area of embedded processor architecture focuses on superscalar techniques, with some of the work specifically targeting FPGA implementation [10]. Some of the works investigated the use of simple scalar cores in multi-core processors targeting standard-cell implementations [11] as well as FPGA [13] to speed up the execution of multi-threaded applications.…”
Section: Other Areas Of Embedded Processor Designmentioning
confidence: 99%
“…Adding three or more ports requires the design of custom memories. An alternative solution is to emulate multi-read and multi-write memories using basic two port memories [10]. There are three different techniques, depicted in Figure 8, for emulating multi-port memories using standard dual-port memories:…”
Section: Register Filementioning
confidence: 99%
See 1 more Smart Citation
“…Design studies targeting higher instruction level parallelism (ILP) microarchitectures typically implement VLIW [5], [6] or vector [7], [8] architectures instead of out-of-order (OoO) [9]- [11] soft processor cores. The problem with superscalar OoO microarchitectures is the complexity of the machinery needed to rename registers, schedule instructions in dataflow order, clean up after mispeculation, and retire results in-order for precise exceptions.…”
Section: Introductionmentioning
confidence: 99%